Identification of Zebrafish Fxyd11a Protein that is Highly Expressed in Ion-Transporting Epithelium of the Gill and Skin and its Possible Role in Ion Homeostasis - Saito, Kaori; Nakamura, Nobuhiro; Ito, Yusuke; Hoshijima, Kazuyuki; Esaki, Masahiro; Zhao, Boqiang; Hirose, Shigehisa (Frontiers in Physiology, 2010)
FXYD proteins, small single-transmembrane proteins, have been proposed to be auxiliary regulatory subunits of Na+-K+-ATPase and have recently been implied in ion osmoregulation of teleost fish. In freshwater (FW) fish, numerous ions are actively taken up through mitochondrion-rich cells (MRCs) of the gill and skin epithelia, using the Na+ electrochemical gradient generated by Na+-K+-ATPase. In the present study, to understand the molecular mechanism for the regulation of Na+-K+-ATPase in MRCs of FW fish, we sought to identify FXYD proteins expressed in MRCs of zebrafish. Reverse-transcriptase PCR studies of adult zebrafish tissues revealed that, out of 8 fxyd genes found in zebrafish database, only zebrafish fxyd11 (zfxyd11) mRNA exhibited a gill-specific expression. Double immunofluorescence staining showed that zFxyd11 is abundantly expressed in MRCs rich in Na+-K+-ATPase (NaK-MRCs) but not in those rich in vacuolar-type H+-transporting ATPase. An in situ proximity ligation assay demonstrated its close association with Na+-K+-ATPase in NaK-MRCs. The zfxyd11 mRNA expression was detectable at 1 day postfertilization, and its expression levels in the whole larvae and adult gills were regulated in response to changes in environmental ionic concentrations. Furthermore, knockdown of zFxyd11 resulted in a significant increase in the number of Na+-K+-ATPase–positive cells in the larval skin. These results suggest that zFxyd11 may regulate the transport ability of NaK-MRCs by modulating Na+-K+-ATPase activity, and may be involved in the regulation of body fluid and electrolyte homeostasis.